Tko pobjeđuje u utrci s vremenom? : Individualne razlike u mentalnoj reprezentaciji vremena - Mikša, Tena (Array, 2018)
When we speak or think about time, we most often do it from one of two possible perspectives: ego-moving or time-moving. From ego-moving perspective, time is perceived as static while we perceive ourselves as moving through time. From time-moving perspective, time is perceived as something that moves towards us while we are static. Time perspective that a person uses can be determined by asking an ambiguous time question. It has been shown that people answer an ambiguous question from ego- and time- moving perspectives equally often. Furthermore, it has been shown that it is possible to prime participants to either ego- or time- moving perspective by giving them simple spatial tasks. Besides, it has been shown that there are some trait differences between participants who adopt ego-moving and those who adopt time-moving perspective. The aim of this research was to examine the frequency of adopting ego-moving and time-moving time representations in Croatia and to examine the possibility of priming time perspectives through spatial tasks. The aim of this study was also to examine individual differences between participants who spontaneously adopt ego-moving and those who adopt time-moving perspective on measures of locus of control, mastery and on the Time Metaphors Questionnaire. Participants were randomly assigned to one of two experimental and one control group. Participants in experimental groups were first primed to time perspective and then answered an ambiguous question, while participants in the control group answered ambiguous questions without priming. All participants answered Time Metaphors Questionnaire, Rotter's Internal-External Locus of Control Scale and Pearlin Mastery Scale. Results showed that 35% of participants adopt ego-moving, while 65% adopt time-moving perspective. Priming did not influence on adopting time perspectives. As expected, participants who adopted ego-moving perspective showed more internal locus of control and scored higher